Differences in the structure of the bat community between a cloud forest refuge and a surrounding semi-arid Caatinga scrubland in the northeastern Brazil. (April 2018) - da Rocha, Patrício A.; Ruiz-Esparza, Juan; Ferrari, Stephen F.
Abstract: The present study compared the structure of the bat communities in semi-arid Caatinga scrub and humid cloud forest habitats in the northeastern Brazilian state of Sergipe. A sampling effort of 185, 790 h.m2 resulted in the capture of 157 bats representing 12 species in the Caatinga, and 259 individuals belonging to 14 species in the cloud forest. Overall, a total species richness of 18, although highly significant differences were recorded between habitats in the abundance of individuals. Glossophaga soricina was the most abundant species in the Caatinga, while Carollia perspicillata was the most abundant in the cloud forest. The Glossophaginae was the principal group in the Caatinga, and the Stenodermatinae in the cloud forest. Frugivores were the most abundant in the cloud forest, and many of these species appeared to be concentrated in this habitat during the dry season, dispersing into the Caatinga during the rainy season. Nectarivores were more abundant in the Caatinga during both seasons, indicating that, even during the dry season, this habitat provides an adequate resource base to support this guild. The present study of the Serra da Guia reinforces the importance of these enclaves of humid forest on the diversity and ecology of Caatinga bats. Highlights: Enclaves of humid forest can be found in several localities throughout the semiarid Caatinga. The bats fauna of a forest enclave was surveyed and compared with that of the surrounding Caatinga. Considerable variation was found between habitats in the abundance of different species, guilds, and body size classes. The frugivorous predominated in the cloud forest, while in the Caatinga it was the nectarivorous. We show significant differences in the structure of the two communities, distant only at 1.5 km.